2020
DOI: 10.4269/ajtmh.20-0053
|View full text |Cite
|
Sign up to set email alerts
|

A Multisite Network Assessment of the Epidemiology and Etiology of Acquired Diarrhea among U.S. Military and Western Travelers (Global Travelers’ Diarrhea Study): A Principal Role of Norovirus among Travelers with Gastrointestinal Illness

Abstract: The U.S. military personnel must be ready to deploy to locations worldwide, including environments with heightened risk of infectious disease. Diarrheal illnesses continue to be among the most significant infectious disease threats to operational capability. To better prevent, detect, and respond to infectious disease threats and improve synchronization across the Department of Defense (DoD) overseas laboratory network, a multisite Global Travelers' Diarrhea protocol was implemented with standardized case defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Also surprising was that SOUTHCOM presented no STEC samples and very few Shigella and Campylobacter cases -however their numbers overall were quite low. These differences might reflect variations in sample collection practices or capabilities in deployed settings [19,31], or may be due to a reluctance of patients to provide stool samples.…”
Section: Pathogen Detectionmentioning
confidence: 99%
“…Also surprising was that SOUTHCOM presented no STEC samples and very few Shigella and Campylobacter cases -however their numbers overall were quite low. These differences might reflect variations in sample collection practices or capabilities in deployed settings [19,31], or may be due to a reluctance of patients to provide stool samples.…”
Section: Pathogen Detectionmentioning
confidence: 99%
“…In recent years, enteroaggregative E. coli has become more frequently identified in the stools of patients with TD, with some studies finding higher rates of enteroaggregative E. coli than enterotoxigenic E. coli in patients from Africa [36] and Latin America [37]. Enteroaggregative E. coli has been found in 7%-54% [38,39] of stool samples of patients with TD, while enteropathogenic E. coli has been identified in 8%-44% [38,39]. Nevertheless, there is ambiguity about the pathogenicity of enteroaggregative E. coli and enteropathogenic E. coli, as they have a high prevalence in asymptomatic travellers [40].…”
Section: Bacteriamentioning
confidence: 99%
“…Viral pathogens associated with TD include norovirus and rotavirus. Norovirus in particular seems to have increased its frequency relative to other aetiologic agents in recent years and in some studies has been the most commonly identified pathogen [34,38]. There is also some uncertainty regarding the pathogenic significance of norovirus, given the identification of high amounts of viral shedding in asymptomatic paediatric patients [47].…”
Section: Virusesmentioning
confidence: 99%
“…Campylobacter has been classified as a leading cause of bacterial gastroenteritis and growth stunting in children living in poverty. Campylobacter jejuni and Campylobacter coli are the predominant Campylobacter species associated with gastroenteritis, both in pediatric populations and in cases of travellers' diarrhea [1][2][3]. Additionally, C. jejuni, C. coli and other Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%